Short Communication: Presence of arbuscular mycorrhiza in maize plantation land cultivated with traditional and improved land management - ISHAQ, LILY (Asian Journal of Agriculture, 2018)
Ishaq L. 2018. Short Communication: Presence of arbuscular mycorrhiza in maize plantation land cultivated with traditional and improved land management.Trop Drylands 2: 20-24. Arbuscular mycorrhizas (AM) are one of key fungtional soil biota that can greatly contribute to crop productiviy and agricultural sustainability. Their presences could be influenced by soil condition such as land management, and the sporulation of the fungal forming mycorrhiza could be affected by season ie. rainy and dry season. Previously, it was found that the abundance of AM fungi was higher under maize cropping with traditional land management (no tillage, no input of agrochemicals) than that under maize copping system with more modern land management (tillage, agrochemical input), when the soils were sampled at rainy season. As the presence of AM fungi could be influenced by climate factor ie. rain/season, the present study was carried out to examine the abundance and diversity of AM fungi in maize plantation land cultivated with traditional and improved land management in the dry season. At each land management system, three locations of study were purposively selected, and at each location within the cropping system, three soil samples were collected. A total of 9 soil samples representing each land management system were evaluated. The variables observed included AM fungal spore density (expressed as the number of AM fungal spores per 100 g of soil) and biodiversity of AM fungi (expressed as relative abundance of AM fungal spore). It was found that the density of AM fungal spore under maize cropping system with traditional land management was 203.55 per 100g, whereas only 84.91 spores per 100 g soil were found under maize cropping system with improved land management, supporting the previous finding. Despite only six AM fungal spores morphotypes were observed under maize plantation land of both traditional and improved land management, the abundance of the morphotype was different between the two land management systems. The study needs to be extended at a broader location and time to get more representative information on the impact of land management on the abundance of AM fungi in tropical agriculture.